(untitled) (Revista Archai, 2024)
This paper offers an interpretation of a certain narrative about the political community, which can be found in Pol. III 10, 1286b7-21; IV 10, 1297b16-28; and VI 4, 1321a5-16, in light of what Aristotle tells us about the causes that lead to revolutions, οἰκονομική, the appearance of money, commerce and the social changes they caused. According to this narrative, the monarchical regime prevailed in most political communities at first, whereas later, in Aristotle’s time, it was the democratic regime which prevailed. Although the explanations given in these passages differ, it is argued that they are compatible and complementary; that, when taken together, they show us causes that could very well complement each other in order to make revolution strongly possible, if not inevitable; that there is an important part of this process, namely, the rise of oligarchies, that they do not explain satisfactorily; and that we can craft a satisfactory explanation of this part of the process if we make use of what Aristotle tells us about οἰκονομική, the appearance of money, commerce and the social changes they caused in book I of the Politics.